Exploring ethnomathematics in tradition games: Hopscotch and marbles for generation Z - Nurul Erika Putri Siregar; Muhammad Nuh (State Islamic University of North Sumatra, 2024)
In the digital era, information and communication technology (ICT) devices have replaced the function of traditional games such as hopscotch and marbles, leading to a decline in Generation Z's interest in these activities. Ethnomathematics serves a strategic role as a bridge between local culture and mathematical concepts, enhancing student engagement and supporting culture-based curricula. This study aims to explore the mathematical concepts embedded in traditional games, such as hopscotch and marbles, played by Generation Z. A qualitative approach employing ethnographic methods was utilized to investigate the relationship between these games and mathematical concepts. Data were collected through participant observation, semi-structured interviews, and documentation studies of Generation Z individuals who still engage in traditional games in North Sumatra, alongside document analysis related to curriculum and mathematics education. The study's findings on traditional games, such as hopscotch and marbles, provide insights based on participants' learning experiences and mathematical content encompassing geometry, measurement, probability, and mathematical operations. From an ethnomathematical perspective, traditional games introduce mathematics contextually and meaningfully. Ethnomathematics in traditional games has the potential to enhance mathematical understanding and contribute to the preservation of local culture among Generation Z.